PET-Saúde interprofissionalidade e a disponibilidade dos estudantes para o aprendizado interprofissional - Marques, Juliana Ferreira Lima (2022)
Introduction: In the Brazilian reality, the theoretical and methodological bases of Interprofessional Education (EIP) provide elements to supply the requirements of the contemporary world and promote the integrality of health care, contributing to the qualification of health professionals to work as a team. Interprofessionality was the focus of the ninth Education Through Work for Health Program (PET-Health/Interprofessionality) to teach them how to work as a team, through integration-teaching-service and the development of collaborative skills. In this scenario, the purpose of this work is to demonstrate elements that allow reflection on interprofessionality and collaborative competencies, through the perception of students participating in the ninth PET-Health/Interprofessionality edition. Purpose: To identify the availability of students who participated in the edition of PETHealth/Interprofessionality for interprofessional education and collaborative interprofessional practices. Methodology: The present study is characterized as a research with a quantitative method, which is part of an exploratory-descriptive perspective in relation to the objectives, based on data collected through the application of the instrument for collecting data on interprofessional health education, Readiness for Interprofessional Learning Scale (RIPLS). Found results: From the data analysis, a positive impact of interprofessional training in health was revealed in terms of collaboration and teamwork induced by the participation of the ninth public notice of PET-Health/Interprofessionality. Moreover, a certain fragility was detected regarding the clarity of definition of the roles of each one, in addition to a need for greater delimitation in relation to professional autonomy and the appreciation of the patient's opinion for participation in care. Final considerations: Several collaborative skills were developed to ensure comprehensive care, based on the analysis of the availability of PETHealth/Interprofessionality participants for interprofessional education and their interprofessional practices. From the analysis of the strengths and weaknesses, it was noticed the need that is still necessary to make this stimulus sustainable, so that there is the sustainability of this stimulus for the effective integration of knowledge and, mainly, much still necessary to guarantee the progression and institutionalization of the perspective of interprofessional practice.